From innovative applications of the effectiveness-implementation hybrid trial design to the dissemination, implementation, effectiveness, sustainment, economics, and level-of-scaling hybrid trial design - Garner, Bryan R. (Frontiers in Health Services, 2022)
To address the enduring gap between research and practice, there is a need to improve the speed and efficiency of research across the translational research spectrum. In 2012, the effectiveness-implementation hybrid trial design (HTD) was codified as a design with the potential to improve the speed and efficiency of translation, especially as part of T2 (clinical research) translational research. Building on this and other recent efforts to stimulate greater use of this novel HTD, the current article highlights an innovative application of each effectiveness-implementation HTD type. The completed application of the Type 1 effectiveness-implementation HTD tested the effectiveness of a clinical intervention for reducing HIV viral load and retaining people with HIV in care, as well as conducted a longitudinal mixed-methods examination to test for significant changes over time in three key measures of context, and economic evaluation of the clinical intervention. The completed application of the Type 2 effectiveness-implementation HTD used a dual-randomized design to simultaneously test the effectiveness of a clinical intervention for addressing substance use disorder among people with HIV and effectiveness of a blended strategy called the Implementation and Sustainment Facilitation (ISF) Strategy. This Type 2 hybrid trial was also innovative due to its focus on both sustainment and economic outcomes. The innovative Type 3 application (funded in 2008 and completed in 2012) tested the effectiveness and cost-effectiveness of using pay-for-performance to improve both implementation outcomes and client outcomes. This article also codifies a HTD called the Dissemination, Implementation, effectiveness, Sustainment, Economics, and Level-of-scaling (DIeSEL) HTD.